Attitude of Basic Science Medical Students towards Post Graduation in Medicine and Surgery: A Questionnaire based Cross-sectional Study from Western Region of Nepal - Roy, Bedanta; Banerjee, Indrajit; Sathian, Brijesh; Mondal, Monami; Kumar, Sai Sailesh; Saha, Chhanchu Gopal (Nepal Journal of Epidemiology, 2011)
Background Career choice of medical students plays a vital role for health care system of a country. It also plays a crucial role to bring medical specialties into mainstream focus. Materials and Method A cross-sectional, questionnaire-based study has been performed at Manipal College of Medical Sciences, during the period of 1st May to 31st August–2011. A self reported questionnaire was given to the undergraduate medical students of Basic sciences. Questionnaire included career choices, nature of career, reason for choice, and education level and occupation in their parents. Results Data was collected from 269 medical students, among them 145 males and 124 female students participated in the study. The mean age of Indian (85, 31.6%), Nepalese (110, 40.9%) and Sri Lankan (74, 27.5%) students were 18.3 ± SD 0.7, 18.6 ± SD 0.8 and 18.0 ± SD 1.5 years respectively. Education and Occupation of parents seems to influence the determination of career choice in case of Medical students (p<0.01). Females have 2.19 times preference of choosing Medicine and 0.22 times Surgery compared to males (p<0.01). In case of Nepali male students, Surgery (60.3%) was the most preferred Postgraduate subject followed by medicine (20.6%) and in female students, medicine (44.7%) and OBG (31.9%). But in case of Indian male students 58.0% & 31.4% female students want to choose surgery as their career. 53.1% of the Sri-Lankan male students want to choose medicine as their post graduation and apart from these 50% of the female students also, which is followed by surgery 46.9% (male) and 21.4% (female) respectively. Conclusion Our study supports that Post-graduation in clinical specialties is always preferred over Basic sciences due to more interaction with patients and the practical aspects of medical profession. The relatively less popularity of some streams may show long-term impact on the health of health system of Nepal. Medical Universities have to modify their academic intervention activities to improve the basic science teaching learning programme in Nepal to turn around the deficiency of post graduates in this stream. http://dx.doi.org/10.3126/nje.v1i4.5754 Nepal Journal of Epidemiology 2011;1(4):126-134